Estudo da defluidização, segregação e caos de misturas binárias areia-serragem em leito fluidizado borbulhante - Santos, Thiago Miranda dos (2015)
Bubbling fluidized beds (LFB) have been used in many industrial applications, with emphasis on energy conversion of solid fuel combustion reactor, gasification and fast pyrolysis. In recent years, the study of fluid dynamics mixture of sand-biomass LFB reactors is gaining importance due to the need to identify the emergence of undesired phenomena in the gas-solid flow, such as sudden defluidization and segregation of particles promoted by the nature polydispersed of the bed material. In order to contribute in this direction, the present work studies the fluid mixtures sandsawing in relation to the previously described phenomena and chaotic behavior intensity of the fluidized bed under various operating conditions. Bed pressure fluctuation measurements were taken to study the defluidization and segregation of particles with the Gaussian spectral technique’s support as well as the presence of chaos using wavelet and 0-1 Test. The bed material consisted of quartz sand and mixtures of pine sawdust with mass percentages of 2.5% and 5% and the inventories of 0.5 and 1.0 kg. Experimental tests were performed in a Plexiglas column of internal diameter 0.11 m and 1.0 m of height. The static pressure values of the bed were recorded using a data acquisition system composed of fast response pressure transducers and software LabVIEWTM version 10.0. The tests followed a 22 factorial design with triplicate, totaling 12 experiments with mixtures sand-sawdust. Thus, with the results were obtained fluid dynamics and curves of central frequency, both used to identify the state of minimum fluidization of the bed. Additionally, the biomass concentration variation curves were prepared according to the layers height of the bed for evaluating the intensity of the segregation. The results showed that in all cases the defluidization region is reached in superficial gas velocity around of 0.05 m/s. Compared to the study of segregation, the results suggest that it tends to be higher for shallow bed than deep beds, not being clearly seen the effect of the percentage of biomass in the mixture within the range tested. A statistical analysis and Pareto chart were used to confirm the significance of the trends observed. The pressure data in the minimum fluidization condition were used to determine the chaotic behavior of the tested mixtures. Thus, the results showed that in all test, the behavior were chaotic, showing in the quantitative analysis, 0-1 test, results of the K* parameter above 0.9 and in the qualitative analysis using wavelet, presented distributed energy regions.